Conserving yacon (Smallanthus sonchifolius) through cryopreservation using the PVS2 droplet vitrification method - Hammond, Stacy; Panis, Bartholomeus; Zamecnik, Jiri; Faltus, Milos; Viehmannova, Iva (Elsevier, 2022)
Proceedings of Cryo2022 Joint Meeting of SLTB and Society for Cryobiology, 19-22 July 2022, Dublin, Ireland